2D Single‐Atom Catalyst with Optimized Iron Sites Produced by Thermal Melting of Metal–Organic Frameworks for Oxygen Reduction Reaction. Issue 6 (5th February 2020) - Liu, Dong; Li, Jin‐Cheng; Ding, Shichao; Lyu, Zhaoyuan; Feng, Shuo; Tian, Hangyu; Huyan, Chenxi; Xu, Mingjie; Li, Tao; Du, Dan; Liu, Peng; Shao, Minhua; et al.
Abstract: Zeolitic‐imidazolate‐frameworks‐8 (ZIF‐8) derivatives have recently been demonstrated as one of the most ideal precursors to prepare single‐atom metal catalysts for oxygen reduction reaction (ORR). However, abundant single‐atom metal sites are buried in the derived carbon nanoparticles, rendering them useless for ORR. Here a novel ZIF‐8 "thermal melting" strategy is proposed to prepare a high specific surface area of Fe‐N‐doped graphene nanosheets (Fe‐N/GNs) with single‐atom Fe‐sites on the surface which are accessible to electrolytes, optimizing their utilization and improving ORR activity. As a result, the Fe‐N/GNs material exhibits excellent ORR activity with half‐wave potentials of 0.903 V in alkaline media and 0.837 V in acidic media, which are comparable to commercial Pt/C catalysts. Abstract : A thermal melting strategy is proposed to design single‐atom Fe catalysts from Fe modified ZIF‐8 precursor. The obtained 2D catalyst holds abundant atomic iron sites on the surface of a carbon layer, and therefore exhibits excellent oxygen reduction activity both in alkaline and acidic mediums, which are comparable to commercial Pt/C catalysts.